Changes in stroke performance in 13-14 year old swimmers over an annual training cycle - Malinovsky M.S. ,; Arishin A.V. ,; Pogrebnoy A.I. , (Theory and Practice of Physical Culture, 2025)
The aim of the study is to identify the dynamics of kinematic parameters of stroke technique in swimmers aged 13-14 years in the structure of the annual cycle. Methods and structure of the study. The experiment involved 28 swimmers aged 13-14 years, I-II sports category. To assess the level of technical training, a method of computer video analysis of swimmers' movements during the 25 m breaststroke at maximum speed was used. In addition, the swimmers' anthropometric parameters were measured and the training loads were analyzed. The material was processed using mathematical statistics methods. Results of the study and conclusions. In swimmers training according to the generally accepted program, only 7 of the 12 studied kinematic parameters showed reliable changes during the year. The observed increase in the parameters of the speed and acceleration of the hand movement in the pull-up phase indicates a decrease in the quality of the stroke, while the parameters of the speed and acceleration of the hand movement in the push-off phase did not show reliable changes. The detected discrepancies in the speed indicators in the main phases of the stroke may be the result of excessive power loads, in which the maximum effort is manifested at the beginning of the movement and negatively affects the formation of kinematic indicators in the pull-up phase, which in turn dictates the need to combine physical and technical training. The pace of movements demonstrated a reliable decrease during the year, while the length of the "step" significantly increased only by the end of the year. The detected increase in the depth of immersion of the hand by the end of the year can be explained by the natural increase in anthropometric indicators. Maximum swimming speed demonstrated reliable dynamics only by the end of the year. Thus, with the generally accepted version of the training process structure, the changes in the stroke structure detected during the year indicate an ineffective ratio of its components. This is evidenced by an increase in the speed and acceleration of the hand movement in the pull-up phase and the absence of the same in the push-off phase. This is also confirmed by an insufficient increase in the maximum swimming speed, which significantly improved only by the end of the year.